Coping with occupational stress: the role of optimism and coping flexibility - Reed DJ (Psychology Research and Behavior Management, 2016)
Daniel J Reed Department of Psychology, Sheffield Hallam University, Collegiate Campus, Sheffield, UK Abstract: The current study aimed at measuring whether coping flexibility is a reliable and valid construct in a UK sample and subsequently investigating the association between coping flexibility, optimism, and psychological health – measured by perceived stress and life satisfaction. A UK university undergraduate student sample (N=95) completed an online questionnaire. The study is among the first to examine the validity and reliability of the English version of a scale measuring coping flexibility in a Western population and is also the first to investigate the association between optimism and coping flexibility. The results revealed that the scale had good reliability overall; however, factor analysis revealed no support for the existing two-factor structure of the scale. Coping flexibility and optimism were found to be strongly correlated, and hierarchical regression analyses revealed that the interaction between them predicted a large proportion of the variance in both perceived stress and life satisfaction. In addition, structural equation modeling revealed that optimism completely mediated the relationship between coping flexibility and both perceived stress and life satisfaction. The findings add to the occupational stress literature to further our understanding of how optimism is important in psychological health. Furthermore, given that optimism is a personality trait, and consequently relatively stable, the study also provides preliminary support for the potential of targeting coping flexibility to improve psychological health in Western populations. These findings must be replicated, and further analyses of the English version of the Coping Flexibility Scale are needed. Keywords: stress management, psychological health, student stress, life satisfaction, organizations